School: A Comic Viewbook - Gregory, Chase P. (Tufts Archival Research Center, 2005)
School is a comic book presented in the form of a Tufts Admissions viewbook. Working in the tradition of creative nonfiction, School compiles data on the university_ï¿½_s branding strategy, its history, and the lived experiences of its students through both visual images and text. Over the course of three weeks, I compiled 35 student interviews, then worked with each profiled person in order to design an artistic profile. School, in addition to being a frame for viewing the college experience, is also designed as a critical inquiry into the ethics of representation, specifically with regard to advertising or the so-called "visual identity" of an institution like Tufts. Its use of meta-language, heterogeneous style, and cyclical self-reflection is meant to mirror the kind of critical thinking that is ethically necessary in any kind of storytelling, as well as to draw attention to the impossibilities of any kind of complete or accurate self-representation or representation of others. Ultimately, the project is meant to provide a lens for critiquing institutionalized forms of representation in favor of a more collective, contradictory, and unstable retelling of the college experience.; Senior Special Project (B.A.)--Tufts University, 2012.